Academic Senate Minutes 2004-02-19 - Academic Senate:::::::::
Chair's Report. Agenda amended and approve. Minutes deferred. Change in MS-CES program approved. Reports from President and Provost. From S&F: Amendment to Article III, Section 3.10 of By-Laws; Replacement of Lecturer Senators – First Reading. Resolution to Asses Faculty Confidence in the SSU Academic Senate and the SSU Administration – First Reading. Grants and Contracts Policy – First Reading. Draft Vision and Mission Statement from the Academic Affairs Strategic Planning committee – First Reading. Joint Doctoral Program in Education – First Reading. Senate Budget committee report. Chair-Elect report. Announcement from Student Senator.